7T MRI in the evaluation of ischemic stroke: a systematic review - Kurz, Felix Tobias; La Grange, Daniela Dumitriu; Botta, Daniele; Vargas, Maria Isabel; Lazeyras, Francois; Edjlali-Goujon, Myriam; Pruvo, Jean-Pierre; Wanke, Isabel; Lövblad, Karl-Olof (Frontiers in Neuroscience, 2025)
Introduction7T magnetic resonance imaging (MRI) has advanced in managing neurological and neurovascular diseases. With improved spatial resolution and signal-to-noise ratio, 7T MRI enhances spatial and functional imaging, benefiting ischemic stroke diagnosis, monitoring, and treatment planning.MethodsTo highlight the advances made with ultra-high field MRI in the evaluation of ischemic stroke patients, a systematic review was conducted on the MEDLINE and Web of Science databases using PRISMA guidelines to find peer-reviewed articles from January 1, 1992, to September 1st, 2024. Search terms included “ischemic stroke,” “7T,” “ultra-high field,” “vessel,” “angiography,” and “MRI.” Studies on 7T MRI in adult ischemic stroke patients were included; exclusions were non-human, post-mortem, or pediatric studies.ResultsWe identified 16 studies on the use of 7T MRI for prolonged periods after stroke symptom onset, highlighting its higher spatial resolution for depicting ischemic lesions and vascular imaging. Vessel wall imaging (VWI) at 7T was effective for assessing vascular alterations post-thrombectomy and evaluating atherosclerotic lesions, with notable applications in identifying culprit plaques and studying glutamate metabolism changes.Conclusion7T MRI advancements open new perspectives for clinical applications and research, particularly in evaluating the impact of thrombectomy strategies and developing treatments to prevent stroke recurrence. Continued research and protocol validation are essential for integrating 7T MRI into routine practice, improving management of neurological and neurovascular diseases.